Kitāb al-Luma‘ fī al-Radd ‘alā Ahl al-Zaygh wa al-Bida‘ Karangan Imām Abū al-Ḥasan al-Ash‘arī: Terjemahan Perbahasan al-Qadr: Kitāb al-Luma‘ fī al-Radd ‘alā Ahl al-Zaygh wa al-Bida‘, An Essay of Imām Abū al-Ḥasan al-Ash‘arī: Translation on the Discussion of al-Qadr - Kamarzaman, Mohd Haidhar; Mahmood, Abdull Rahman; Azmi, Mohd Faizul (Afkar: Jurnal Akidah dan Pemikiran Islam, 2018)
At the end of the Salaf era, too many misguided firqah emerged mainly from the Qadariyyah and Jabariyyah groups that addressed the issue of Allah’s qadr. Imām al-Ash‘arī was born around the third century Hijrah who bring the faith of Ahli Sunnah Wa al-Jama‘ah to defend the issue of the qadr of Allah until he had authored the book of al-Luma‘ and addressed a specific issue in the matter of the human acts against the Qadariyyah and Jabariyyah groups. This study attempts to translate al-Luma‘ works by al-Ash‘arī which takes only the part of qadr of Allah the Almighty only. The study also attempts to provide an understanding of the issue of Allah’s qadr in the perspective of al-Ash‘arī in opposing the deviant group. This study uses data collection methods, data analysis which includes comparative analysis, historical-based analysis, content analysis, and inductive and deductive methods. The study finds that al-Ash‘arī has unraveled the entire problem of qadr Allah in the book al-Luma‘ in order to provide an understanding to the public in eradicating the deviant teachings of the Qadariyyah understanding which led to the misunderstanding of the issue of and human act. This study has also completed the translation of a chapter from al-Luma‘ in the qadr problem in order to show the view of Imam al-Ash‘arī in answer the arguments of the Qadariyyah and Jabariyyah groups in the issue of qadr and the acts of slaves.